Effect of Nature of Trellis on the Performance of Boro Rice and Vegetable Crops Grown in the Ails of Boro Rice Field (Journal of Agriculture & Rural Development, 2010)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from December 2004 to May 2005 to determine the most effective kind of trellis for the rice-cum-vegetable production system. The treatments consisted of five crop combinations viz. C0: rice alone i.e. control, C1: rice + bottle gourd, C2: rice + white gourd, C3: rice + snake gourd and C4: rice + bitter gourd, and four levels of trellises viz. T1: flat trellis, T2: T-trellis (180 cm breadth), T3: T-trellis (240 cm breadth) and T4: X-trellis (cross trellis). The experiment was laid out in randomized complete block design with three replications. Vegetable seeds were sown directly in the pit made on ails of Boro rice field. Later, vegetable crops were supported by trellis made with bamboo and plastic rope arrangements. Results showed that yield and yield contributing characters of Boro rice along with vegetable and rice equivalent yields varied significantly due to crop combination, nature of trellis and their interactions. The trellis-grown bitter gourd (C4) and bottle gourd (C1) did not significantly reduce rice yields compared to that obtained from sole rice plot. Grain yields reductions due to trellis-grown vegetable were just marginal. Regarding vegetable yield, white gourd (C2) on the ails of Boro rice plots gave the highest yield of 14.52 tha-1 followed by 9.73 tha-1 of bottle gourd (C1). In respect of cost of production, both flat trellis (T1) and T-trellis with 180 cm breadth (T2) were found to be the most suitable trellises for Boro rice-cum-vegetable cultivation on the ails of growing rice crop. Key words: Trellis, performance, vegetable crops, Ail, Boro rice. DOI: 10.3329/jard.v7i1.4417 J Agric Rural Dev 7(1&2), 15-21, June 2009